Poetry and politics in Néstor Perlongher (Anclajes, 2012)
From an analytical standpoint, we are interested in revising the first critical neo-baroque-framed responses to Néstor Perlongher’s politics and poetry so as to propose an updated reading of his work even more attentive to the current theoretical and critical debates. It is thought to conclude on an interpretation of the political violence in Perlongher’s poetry as a literary assimilation of the surrounding historical reality in its intricate relationship with sexual violence. Finally, some hypotheses about the Argentinean poetic traditions and the non-normative sexuality cultures upon which to consider Néstor Perlongher’s poetry will be outlined.
Keywords: Néstor Perlongher; argentine poetry; neo-baroque; sexual-politics; non-normative sexualities